Use of personal protective equipment under occupational exposure to cytostatics - Sylwia Krzemińska; Małgorzata Pośniak; Małgorzata Szewczyńska (Nofer Institute of Occupational Medicine, 2016)
Background: A growing number of cancer cases enhances the usage of cytostatic agents and thereby contributes to the increase in the number of health care workers occupationally exposed to cytostatics. Material and Methods: This article presents the results of the survey aimed at obtaining data on the reduction of occupational exposure through using personal protective equipment by the medical and pharmaceutical personnel involved in handling cytostatics. The questionnaires were sent by mail or e-mail to oncology hospitals and pharmacies preparing cytostatic drugs. Responses were received from 94 people employed in these workplaces. The main questions concerned the forms of cytostatics; job activities; types of personal protective equipment used and working time under exposure to cytotoxic drugs. Results: The majority (over 90%) of the healthcare personnel declared the use of personal protective equipment when working under conditions of exposure to cytostatic drugs. Depending on the type of protection, 15-35% of people reported that the most frequent time of their single use of the apron, the overalls, the gloves, the cap, the goggles or the respirators did not exceed few minutes. Gloves were changed most frequently. However, half of the responses indicated that the time after which the respondents removed protection equipment greatly differed. Conclusions: Almost the whole group of respondents applied personal protective equipment when working under exposure to cytostatics. However, personal protective equipment was not used every time in case of exposure. The medical and pharmaceutical staff worked under exposure to cytostatics for a few or even dozen hours during the working day. Med Pr 2016;67(4):499-508